Психологічні особливості злочинців-рецидивістів корисливого та насильницького типів : автореф. дисертації - Філоненко, В. М.; Filonenko, V. M.; Шевченко, Л. О. - науковий керівник (Харків : Харківський національний університет внутрішніх справ, 2015)
У дисертації здійснено детальний теоретичний аналіз проблеми особистості злочинця у сучасній вітчизняній та зарубіжній юридичній психології та надані результати багаторакурсного емпіричного дослідження психологічних особливостей неодноразово засуджених злочинців корисливого та насильницького типів. Виявлено специфіку агресивності злочинців-рецидивістів корисливого та насильницького типів, їх акцентуацій характеру; емоційного інтелекту, інгибіції у спілкуванні, локалізації контролю, ціннісної сфери; встановлено особливості саморегуляції особистості та копінг-стратегій злочинців-рецидивістів. На основі багатопланового емпіричного дослідження автором розроблено психологічну типологію злочинців - рецидивістів різної кримінальної спрямованості та різних типів відтворюваності злочину. Визначені в роботі психологічні особливості рецидивістів та розроблені автором рекомендації для психологів пенітенціарної служби дозволяють більш ефективно виявляти причини вчинення злочину, більш диференційовано організовувати психокорегувальну та профілактичну роботу у виправних установах.

In the thesis detailed theoretical analysis of the problem of studying criminal's personality in modern domestic and foreign juridical psychology was done. There were presented the results of empirical research of multi-angle psychological characteristics of repeatedly convicted offenders of acquisitive and violent types. The motivation for this study is based on the negative impact of crime in Ukraine and the role that recidivism plays as a contributing factor within this context. The choice of the research topic was motivated from a literature perspective, focusing specifically on the role that recidivism studies can play in crime prevention and management. Theoretical analysis conducted in order to conceptualize and operationalize recidivism as well as develop a classification system whereby a recidivist could be psychologically classified. Due to the concept of recidivism various complementary theories were studied. Since not one theory only is applicable to recidivism, the research followed an eclectic approach to design an integrated three-level concept on recidivism. In the study recidivism defined within a psychological context. Based on this conceptualization a typology was identified whereby an offender can be classified as a non – chronic, chronic, extreme – chronic recidivist. The non-chronic recidivists are offenders that have been convicted two times, chronic recidivists have convicted more than twice but less than five times, whereas the extreme chronic recidivists have been convicted more than five times. The difference between the three categories of recidivists therefore lies not only in the number of convicted offences. It became apparent that recidivists of these types not only both refer to repeat criminal conduct but also have specific psychological habitual patterns. Theoretical analysis shown that recidivism as phenomenon is conceptualized in psychological context fragmentary. Noticed that recidivists' typology needs psychological definition. No profile of the recidivist exists which could assist with the development of need directed The author considered, that in order to address recidivism it is important to have a psychological classification system in place as well as to design psychological correctional programs for the prevention and management of recidivism. Based on the problem statement the aim and objectives of the study were formulized. The study was designed to investigate complex of psychological characteristics in a sample of incarcerated males. The sample consisted of two subsamples of inmates. One subsample was acquisitive recidivists and the other subsample was violent recidivists. Both subsample consisted three groups of inmates: non-chronic recidivists (convicted two times), chronic recidivists (convicted three – five times), extreme – chronic recidivists (convicted more than six times). Psychological diagnostic instruments were used in the study according the focusing the investigation for accentuations of character, aggression, values, individual styles of self-regulation, locus control, coping strategies, emotional intelligence and inhibition in communication. The specifics of aggression of recidivists of acquisitive and violent type, their accentuation of character, emotional intelligence, inhibition of communication, localization of control valuable sphere were identified. The features of self-regulation of recidivists of different types of chronic crime were defined. Most significant differences were identified between chronic acquisitive and violent recidivists. Factor analysis applied in the work and revealed the hidden interrelated factors of psychological variables. They predispose to crime reproducibility by recidivists of acquisitive or violent direction. Factors "Complex aggressive behavior", "Communication" and "Character traits" suggested that in groups of violent and acquisitive recidivists manifestations of aggression, interpersonal relationship and character facilitated by focusing on different characteristics. The factor "Subjective control" in acquisitive recidivists distinguishes the characteristics indicated that external willingness to overcome difficulties and take responsibility for their actions determine the propensity to self-incrimination. In violent recidivists fourth factor "Values" includes humanistic values in isolation from other psychological characteristics. On the basis of multi - faceted empirical research author developed a psychological typology of recidivists of acquisitive and violent criminal orientation and different types of crime reproducibility. Identified psychological characteristics of offenders and the recommendations developed by the author for psychologists in prison departments of correctional services enable more effective to establish the causes of the crime, a more different organize psychological correction and prevention work in prisons.

В диссертации осуществлен детальный теоретический анализ проблемы личности преступника в современной отечественной и зарубежной юридической психологии и представлены результаты многоаспектного эмпирического исследования психологических особенностей неоднократно осужденных преступников корыстного и насильственного типов. Выявлено специфику агрессивности преступников-рецидивистов корыстного и насильственного типов, их акцентуаций характера; эмоционального интеллекта, ингибиции в общении, локализации контроля, ценностной сферы; установлены особенности саморегуляции личности и копинг-стратегий преступников-рецидивистов. На основе многопланового эмпирического исследования автором разработана психологическая типология преступников - рецидивистов различной криминальной направленности и различных типов воспроизведения преступления. Выявленные в работе психологические особенности рецидивистов и разработанные автором рекомендации для психологов пенитенциарной службы позволяют эффективнее устанавливать причины совершения преступления, более дифференцированно организовывать психокоррекционную и профилактическую работу в исправительных учреждениях.
Автореферат дисертації на здобуття наукового ступеня кандидата психологічних наук
Psychological peculiarities of offenders – recidivists of acquisitive and violent types
Keywords: Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 19.00.06; агресивність; акцентуації характеру; злочинці; інгибіція у спілкуванні; копінг-стратегії; локус контролю; рецидивісти; саморегуляція; емоційний інтелект; accentuation of character; aggression; emotional intelligence; coping strategies; inhibition in communication; locus of control; self-regulation; offenders; recidivists; агрессивность; акцентуации характера; ингибиции в общении; копинг-стратегии; локус контроля; преступники; рецидивисты; саморегуляция; эмоциональный интеллект